Six Sigma Based Analysis for Final Product Quality Control in a Snack Noodle Manufacturing Company - Muhammad Ridwan Gunawan; Wike Agustin Prima Dania (Agroindustrial Journal, 2026)
Six Sigma provides a structured and data driven methodology for improving process capability and product quality in manufacturing systems. This study applied the Six Sigma DMAIC framework integrated with the seven quality control tools to evaluate final product quality in snack noodle manufacturing by considering both production and post production factors, including packaging configuration and handling practices. Data were collected from 520 snack noodle samples. The results identified three dominant defects: noodle integrity below 95%, broken noodles, and non-standard net weight. The calculated sigma level of 1.95 indicated relatively low process capability despite the process being statistically stable. Root cause analysis showed that defects were associated with machine instability, improper handling, material inconsistency, packaging configuration, and non-standardized procedures. Several improvement actions were proposed, including preventive maintenance, operator training and SOP reinforcement, raw material control, and standardized handling procedures. However, the proposed improvements were not implemented or empirically validated within the scope of this study. The findings highlight the importance of integrating production and post production quality control and extend the application of Six Sigma by incorporating downstream operational factors into final product quality evaluation.